Nagorno-Karabakh : Twenty years under damocles' sword - Valiyev, Anar (ResearchGate, 2012)
This article examines the consequences of the Nagorno-Karabakh war for Armenia and Azerbaijan from an Azerbaijani perspective, showing how the conflict prevents democratization and internal development while blocking external ties. Continued conflict is leading to expensive and dangerous arms races and a demonization of each other’s societies.
Demokratizatsiya
Keywords: Nagorno-Karabakh Conflict, 1988-1994.; Ethnic conflict -- Azerbaijan.; Azerbaijan -- Relations -- Armenia (Republic).; Ethnic conflict -- Armenia (Republic).